Knowledge, perceptions and practices of health care workers about detection of respiratory symptomatics in a very high risk region of tuberculosis transmission in Peru - Romani Romani, Franco Ronald (2016)
Introduction. Tacna is a region with very high risk of tuberculosis transmission; however, the diagnostic performance of direct smears in their healthcare centers is 1.5%. Objectives. To describe the knowledge, perceptions and practices about detection of respiratory symptomatic subjects. Design. Cross sectional study. Setting. Health care centers of Tacna Regional Health Directorate. Participants. Health professionals including physicians and nurses. Interventions. A structured self-administered, anonymous questionnaire, developed by the authors, based on the current "Technical Standard for Comprehensive Management of People Affected by Tuberculosis", was applied to 178 health professionals (physicians and nurses). Main outcome measures. Absolute and relative frequency of adequate knowledge, perceptions and practices on detection of respiratory symptomatic subjects. Results. In the study, 89.9% knew the definition of respiratory symptomatic, 93.3% was aware that two sputum specimens should be requested to the respiratory symptomatic persons, 22.5% recognized the indicator that assesses the quality of detection of respiratory symptomatic, and 28.1% knew the indicator that assesses the ability of staff to perform the smear in identified respiratory symptomatic. 49.4% distinguished that the goal of the search intensity indicator is 5 per 100 attentions in people older than 15 years, and 60.8% reported having read the current technical standard. Conclusions. A gap in the knowledge of physicians and nurses in the detection of respiratory symptomatic subjects was found. This gap was greater in knowledge about operational indicators of detection.